Potassium-Competitive Acid Blockers (P-CABS) as a New Breakthrough in the Treatment of Gastroesophageal Reflux Disease and Erosive Esophagitis : A Recent Literature Review - Ayuni Putri, Nia (Asosiasi Dosen Muda Indonesia, 2025)
Gastroesophageal reflux disease (GERD) and erosive esophagitis (EE) are common gastrointestinal disorders typically managed with proton pump inhibitors (PPIs). Although effective, PPIs have certain limitations, prompting the development of a new class of acid-suppressing agents known as potassium-competitive acid blockers (P-CABs). These agents offer the potential for faster and possibly more effective treatment compared to PPIs. This literature review aims to evaluate the efficacy, safety, and potential cost-effectiveness of P-CABs versus PPIs in the treatment of GERD and EE, based on five recent clinical trials. This review includes randomized controlled clinical trials investigating four types of P-CABs: vonoprazan, linaprazan glurate, fexuprazan, and tegoprazan, based on five source articles. The findings indicate that all P-CABs demonstrate efficacy that is comparable to or greater than that of PPIs, with a faster onset of action, favorable safety profiles, and promising cost-effectiveness, particularly in severe cases of EE. These results suggest that P-CABs are a promising alternative therapy for GERD and EE, supported by strong clinical evidence across various treatment scenarios. This review offers a novel contribution by summarizing five recent clinical trials on four P-CAB agents. Addressing the lack of comparative evaluations on their efficacy, safety, and cost-effectiveness, especially in PPI-resistant GERD and EE cases, this review supports more informed clinical decision-making.